2021
DOI: 10.1097/bpo.0000000000001830
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Halo Gravity Traction in Severe, Stiff Scoliosis

Abstract: Purpose: The correction of severe, stiff scoliosis in children is challenging. One method used to reduce the risk is preoperative halo gravity traction (HGT). In this study, the authors sought to define the efficiency and safety of HGT and characterize the chronology of the correction seen. Method: A consecutive group of pediatric patients with severe spinal deformities was treated with HGT before definitive correction. A standard protocol with the daily addition of weight to 50% of body weight at 3 weeks was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This reduces the amount of correctional force required during surgery, thus minimizing the risk of surgical complications. 12 , 13 Other benefits of HGT include improved pulmonary function and nutritional status of the patient. 4 , 14 , 15 The increased nutritional status is most beneficial for patients who are underweight preoperatively and risk developing issues with wound care and instrumentation prominence later in their postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the amount of correctional force required during surgery, thus minimizing the risk of surgical complications. 12 , 13 Other benefits of HGT include improved pulmonary function and nutritional status of the patient. 4 , 14 , 15 The increased nutritional status is most beneficial for patients who are underweight preoperatively and risk developing issues with wound care and instrumentation prominence later in their postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed on 24 patients with a mean age of 11.8 years. The most improvement (82%) occurred in the first 3 weeks and the mean duration of traction was 42 days [ 29 ]. Hwang et al obtained the most correction (28.2%) within 1 week and observed that significant changes in the curvature, a correction of 34%, occurred in up to 2 weeks [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bogunovic et al had a complication rate of 27% (transient nystagmus, upper extremity numbness, pin site erythema/infection, unilateral miotic pupil, and progression of myelopathy) and they used a traction weight for each patient of 33.5% of their body weight [ 28 ]. Rocos et al, of the 24 patients, had 1 patient with early signs of cranial nerve palsy, 8 patients with pin loosening, and one with transitory urinary disturbance [ 29 ]. In their study of 59 patients, Hwang et al recorded complications in 10 cases: vomiting, intolerable pin site pain, pin site infection, skull fracture, and pelvic wound [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement can be measured in curve correction (in both coronal and sagittal planes), functional improvements (pulmonary and feeding function), and trunk length and shift. Previous studies of pediatric populations have shown average improvements in curve severity ranging from 35% to 50% angular correction of both coronal and sagittal plane deformities 10,31,40 . Changes in trunk length are noted to average 5 to 6 cm 30,31 .…”
Section: Efficacy Of Hgtmentioning
confidence: 98%